Конфігураційні можливості концепту BILDUNGSWEG як конституента концептополя BERUFSWAHL - Цісар, А. М.; Tsisar, A. M. (Східноєвропейський національний університет ім. Лесі Українки, 2011)
У статті на основі існуючих у сучасній лінгвістичній науці вчень про концепти, концептополя та концеп- тосистеми проаналізовано висловлювання представників німецької молоді про вибір їх майбутніх професій, виявлено конфігураційні можливості концепту BILDUNGSWEG як конституента концептополя BERUFSWAHL. In the article analyzed the statements of representatives of the German youth about choosing their future professions and determined the configurational possibilities of the concept BILDUNGSWEG which belong to the conceptual field BERUFSWAHL in terms of existing linguistic studies of concepts, conceptual fields and systems of linguistic concepts.
Configurational Possibilities of the Concept BILDUNGSWEG as the Constituent of the Conceptual Field BERUFSWAHL
Keywords: концепт; мікроконцепт; концептополе; фрейм; дискурсивні конфігурації концепту; concept; microconcept; conceptual field; frame; discursive configurations of a concept